2010
DOI: 10.1038/nsmb.1795
|View full text |Cite
|
Sign up to set email alerts
|

Structures of apicomplexan calcium-dependent protein kinases reveal mechanism of activation by calcium

Abstract: Calcium-dependent protein kinases (CDPKs) play pivotal roles in the calcium-signaling pathway in plants, ciliates and apicomplexan parasites, and comprise a CaMK-like kinase domain regulated by a calcium-binding domain in the C-terminus. To understand this intramolecular mechanism of activation, we solved the structures of the autoinhibited (apo) and activated (calcium-bound) conformations of CDPKs from the apicomplexan parasites Toxoplasma gondii and Cryptosporidium parvum. In the apo form, the C-terminal CDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(262 citation statements)
references
References 29 publications
11
251
0
Order By: Relevance
“…As shown with the T. gondii CDPK1 orthologue (TgCDPK1), activation of the enzyme upon calcium binding occurs through a large conformational change. The binding of calcium reorganizes the C-terminal CDPK activation domain (CAP) causing its relocation to a site distant from the substrate binding site [54]. Moreover, TgCDPK1 has been shown to be an essential regulator of calcium-dependent exocytosis by controlling the calcium-dependent secretion of micronemes, and blocking TgCDPK1 inhibits parasite motility, host-cell invasion and egress [9].…”
Section: The Camk Groupmentioning
confidence: 99%
“…As shown with the T. gondii CDPK1 orthologue (TgCDPK1), activation of the enzyme upon calcium binding occurs through a large conformational change. The binding of calcium reorganizes the C-terminal CDPK activation domain (CAP) causing its relocation to a site distant from the substrate binding site [54]. Moreover, TgCDPK1 has been shown to be an essential regulator of calcium-dependent exocytosis by controlling the calcium-dependent secretion of micronemes, and blocking TgCDPK1 inhibits parasite motility, host-cell invasion and egress [9].…”
Section: The Camk Groupmentioning
confidence: 99%
“…However, instead of the kinase domain being regulated by a separate calmodulin protein, CDPKs have a fused domain structure between an N-terminal serine threonine protein kinase and a C-terminal calcium activation domain (CAD) that consists of a calmodulin-like module linked to the kinase domain by a junctional domain (11,12). A number of CDPKs have been crystallized, and analysis of their structures has led to an understanding of their unique activation mechanism (11,12). In the absence of calcium, CDPKs are autoinhibited due to the fact that the CAD occludes the active face of the kinase domain.…”
Section: -Isoleucine [I]-lysine [K]-lysine [K]) Kinases In Plasmodiummentioning
confidence: 99%
“…This is based on in vitro studies that have shown that autophosphorylation of Thr-271 is Ca 2+ dependent (Takezawa et al, 1996) and by analogy to structural studies of CDPK (Wernimont et al, 2010(Wernimont et al, 2011) that reveal that Ca 2+ binding can cause a large conformational change, moving the C-terminal domain away from the active site enabling ATP and substrate access. Following Shimoda et al (2012), we assumed that the phosphorylatable species is in the non-Ca 2+ -activated form.…”
Section: Ccamk Autophosphorylation Modelingmentioning
confidence: 99%
“…These are structures of CDPKs (Wernimont et al, 2010(Wernimont et al, , 2011 with and without Ca 2+ that had a high structural similarity (C-a root mean square deviation [RMSD] of 0.81 Å) to the top ab initio-predicted structure from I-Tasser (Zhang, 2008;Roy et al, 2010). Despite some key differences, such as the lack of a CaM binding domain, CDPKs have some striking features in common with CCaMK, such as the kinase domain, a linker region, and an EF-hand domain.…”
Section: Structural Analysis and Energy Minimizationmentioning
confidence: 99%